PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU LIVEWORKSHEET PADA MATA PELAJARAN PENDIDIKAN PANCASILA DIKELAS IV SD - Dwi, putri syntiya; Susilawati, Wiwik Okta; Darniyanti, Yulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research on the development of Electronic Student Worksheets (E-LKPD) based on the Problem Based Learning Model Assisted by liveworksheets in Pancasila Education subjects in Grade IV of Elementary School. E-LKPD can help and facilitate tehe learning process as Pancasila Education Teaching Materials. The type of research used by the researcher is the type of Research & Development (R&D) development research. The development model used in this study is the four-D of 4D model, Define, Design, Develop and Disseminate. The results of the validator of content or material experts obtained an average of 89,99%, the results of the validation of language experts obtained an average of 77,13% the results of the validation of graphic experts obtained an average of 89,33%, the results of the validation of teaching module experts obtained an average of 89,37% and the results of the validation of questions obtained an average of 84,16%